Approximate analysis of some two-degree-of-freedom nonlinear random systems by an extension of Gaussian equivalent linearization - Hung, Luu Xuan (Vietnam Journal of Mechanics, 2001)
The paper presents the analysis of some two-degree-of-freedom nonlinear systems under random excitation using Local Mean Square Error Criterion which is an extension of Gaussian Equivalent Linearization. The results obtained shows that the new technique can be very efficiently used not only for simple-degree-of-freedom systems as presented in the previous papers, but also for multi-degree-of-freedom ones. The solution accuracy obtained by the proposed technique is much more improved than that using the traditional linearization. The conclusions in the paper point up the significance of this technique